PEMANFAATAN KECERDASAN BUATAN DALAM IMPLEMENTASI KEPEMIMPINAN SEKOLAH DI SMA MUHAMMADIYAH 02 MEDAN - Ratnawati, Sri; Suyatno, Suyatno; Hidayati, Dian (STKIP Pesisir Selatan, 2025)
Educational leadership is one of the strategies that determines the emergence of institutional change for the better. In this case, the quality of leadership must be improved over time to ensure the progress of the world of education at the national level. This progress is measured through a value system. This is done to ensure educational goals can be realized in the era of the AI ​​​​technology revolution. Artificial Intelligence (AI) technology, commonly known as artificial intelligence, has experienced massive development from year to year. Where the presence of AI technology is closely related to features, functions, and displays that increasingly impact many aspects of human life, including education. These elements can be mentioned as Tangible, Intangible, Reliability, and Responsiveness. Organizational leadership is closely related to understanding the work procedures between units within an institutional organization. Therefore, in relation to this research, every leader must be able to implement artificial intelligence or AI in accordance with current developments. Therefore, as a public leader, they can establish good cooperation and become a reference for the public with a functional and operational management system that includes planning, organizing, staffing, leading, controlling in internal and external activities, with reference to the institution's vision and mission in accordance with current technological developments.